Menemukan Harmoni dalam Kebenaran Epistemologi Integrasi Islam dan Sains - Nida'ul Haq Nur Fitria; Hamam Syamsuri (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2023)
Islam and science are often considered to have a separator between the two so it has a setback impact on Islamic civilization. The conflict process that exists between Islam and science is capable of giving birth to an extraordinarily complex relationship in the story of human civilization. Even though in reality not all issues between Islam and science always have contradictions in them. The integration of Islam and science is able to lead Muslims towards civilizational achievements. The purpose of this paper is to find harmony in the epistemological truth of the integration of Islam and science. The method used in this research is library, in which this research is faced directly with data sources that already exist in the library or can be said to be ready-to-use data. The results of the study show that the epistemology of the integration of Islam and science has a close relationship with one another.